A Safer High‐Energy Lithium‐Ion Capacitor Using Fast‐Charging and Stable ω‐Li3V2O5 Anode. Issue 4 (21st February 2023) - Lan, Xiwei; Liu, Xueting; Meng, Tao; Yang, Shanshan; Shen, Yue; Hu, Xianluo
Abstract: Lithium‐ion capacitors (LICs) are flourishing toward high energy density and high safety, which depend significantly on the performance of the intercalation‐type anodes used in LICs. However, commercially available graphite and Li4 Ti5 O12 anodes in LICs suffer from inferior electrochemical performance and safety risks due to limited rate capability, energy density, thermal decomposition, and gassing issues. Here a safer high‐energy LIC based on a fast‐charging ω ‐Li3 V2 O5 ( ω ‐LVO) anode with a stable bulk/interface structure is reported. The electrochemical performance, thermal safety, and gassing behavior of the ω ‐LVO‐based LIC device are investigated, followed by the exploration of the stability of the ω ‐LVO anode. The ω ‐LVO anode exhibits fast lithium‐ion transport kinetics at room/elevated temperatures. Paired with an active carbon (AC) cathode, the AC|| ω ‐LVO LIC with high energy density and long‐term endurability is achieved. The accelerating rate calorimetry, in situ gas assessment, and ultrasonic scanning imaging technologies further verify the high safety of the as‐fabricated LIC device. Theoretical and experimental results unveil that the high safety originates from the high structure/interface stability of the ω ‐LVO anode. This work provides important insights into electrochemical/thermochemical behaviors of ω ‐LVO‐based anodes within LICs and offers new opportunities to develop safer high‐energy LIC devices. Abstract : A safer high‐energy Li‐ion capacitor (LIC) is fabricated by using a fast‐charging and stable ω ‐Li3 V2 O5 anode. The as‐prepared LICs exhibit significantly reduced heat release and gas generation, addressing the safety issues of the existing commercial anodes (graphite and Li4 Ti5 O12 ). The mechanism for enhanced safety of ω ‐Li3 V2 O5 benefiting from the stable bulk/interface structure is unveiled.